Retail Banking Loan Portfolio Equilibrium Mix: A Markov Chain Model Analysis - Mohamed, Saiful Maznan (2002)
Realising that a systematic loan allocation technique would normally increases the expected income on interest, this maiden study shall attempt to devise loan allocation policy using a Markov Chain Market Share model.